IMPACT OF ENTREPRENEURSHIP IN THE DIGITAL AGE: A BUSINESS MODEL ON STRUCTURAL EQUATION MODELING APPROACH - Dr.S.Amudhan1,Dr.S.Thandayuthapani2,Dr.Anamika Rawat3,Sheeba N4, Dr.P.Muralidharan5,Dr.J.Poornima6 (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2024)
This article’s goal is to propose a research model that examines the relationships between the development of an impact of entrepreneurs in the digital age and various aspects that contribute to an entrepreneur’s success, particularly communication with the government. A tool with seven components—lack of marketing expertise, finances, sources, technology, social media, digital marketing, and government support—was created and provided to organizations from the entrepreneurial community. Data were collected from 200 respondents of the entrepreneurs from Bengaluru city. One Way ANOVA modeling was used to analyze the gathered data and Structural equation modeling (SEM) was utilized for data analysis to assess the relationship between the model’s variables. The research’s findings demonstrated that absolute fit indices fit the sample data and demonstrate that the suggested model has an acceptable fit by meeting the suggested values. The result showed that all two constructs Government support and Social Media positively and strongly associated with the Entrepreneurs success in the Digital model. Keywords: Digitalization, Entrepreneurship, Digital age, Government Support, Technology, Sources, Lack of Marketing Competency.